Unveiling the Microbial Ecology behind Mezcal: A Spirit Drink with a Growing Global Demand - Patricia Alejandra Becerra-Lucio; Elia Diego-García; Karina Guillén-Navarro; Yuri Jorge Peña-Ramírez (Fermentation, 2022)
The advent of omics has expanded our knowledge of microbial ecology behind Mezcal, a fermented spirit made from the juices of cooked Agave plants (Agave spp., Asparagaceae). Mezcal has been produced in Mexico for over 200 years, however, has been in high demand since its discovery by international markets in the last decade. Mezcal is appreciated for its diverse and complex sensory profile, which is tied to the geographic and environmental diversity of the different Mezcal-producing regions. This regional typicity is brought about by spontaneous fermentation consortia that act in loosely controlled artisanal fermentation processes. Previous works have mainly concentrated on microorganisms involved in the biosynthesis of alcohol and other volatile compounds, or from a different perspective, on culturable microorganisms (mainly yeasts) influencing the taste profile. Attention has been aimed at the richness of microbial populations in point events or under laboratory conditions, which leaves much of the biological richness out of account. Omics techniques have become powerful tools for characterizing the composition of autochthonous fermentation microbiota, regional or endemic features, and ecological processes that determine the dynamics of Mezcal fermentation. The analyses of genetic material, proteins, and metabolites allow disentangling the biological complexity of Mezcal production. This review presents the reader with an up-to-date overview of publications that discuss microbial communities in Mezcal fermentation, metabolic pathways regulated by microbial interactions, and the application of omics to characterize the spontaneous fermenting microbiota conformation and dynamics considering the subjacent ecological processes.